Development and validation of a simplified titration method for monitoring volatile fatty acids in anaerobic digestion. (September 2017) - Sun, Hao; Guo, Jianbin; Wu, Shubiao; Liu, Fang; Dong, Renjie
Graphical abstract: Highlights: TS content in titrated samples constitutes main accuracy factors in VFA titration. Linear correlation was established between TS contents and titration differences. Simplified method for VFA monitoring in AD process was developed and validated. This new method would benefit development of low-cost automatic titration devices. Abstract: The volatile fatty acids (VFAs) concentration has been considered as one of the most sensitive process performance indicators in anaerobic digestion (AD) process. However, the accurate determination of VFAs concentration in AD processes normally requires advanced equipment and complex pretreatment procedures. A simplified method with fewer sample pretreatment procedures and improved accuracy is greatly needed, particularly for on-site application. This report outlines improvements to the Nordmann method, one of the most popular titrations used for VFA monitoring. The influence of ion and solid interfering subsystems in titrated samples on results accuracy was discussed. The total solid content in titrated samples was the main factor affecting accuracy in VFA monitoring. Moreover, a high linear correlation was established between the total solids contents and VFA measurement differences between the traditional Nordmann equation and gas chromatography (GC). Accordingly, a simplified titration method was developed and validated using a semi-continuous experiment of chicken manure anaerobic digestion with various organic loading rates. The good fitting of the results obtained by this method in comparison with GC results strongly supported the potential application of this method to VFA monitoring.